Self-focused attention, cost/probability bias, and avoidance behavior mediate the relationship between trait mindfulness and social anxiety: A cross-sectional study - Noda, Shota; Shirotsuki, Kentaro; Sasagawa, Satoko (Frontiers in Psychology, 2022)
Self-focused attention, cost/probability bias, and avoidance behavior are maintaining factors for social anxiety. In particular, cost bias and avoidance behavior predict social anxiety. It has been shown that the enhancement of trait mindfulness improves these maintaining factors. This study examines the relationships among trait mindfulness, self-focused attention, cost/probability bias, avoidance behavior, and social anxiety, and clarifies whether they mediate the relationship between trait mindfulness and social anxiety. A cross-sectional design was used to examine the relationships among these variables. Participants were recruited from three universities in Japan (January 2019–December 2019). Undergraduate students (N = 367) completed a set of self-report measures assessing trait mindfulness, self-focused attention, cost/probability bias, avoidance behavior, and social anxiety. Results of path analyses revealed that the hypothesized model’s goodness-of-fit indices had high values. Trait mindfulness showed a direct negative association with self-focused attention, cost/probability bias, avoidance behavior, and social anxiety. Moreover, trait mindfulness was negatively associated with social anxiety via self-focused attention, cost/probability bias, and avoidance behavior. These findings indicate that mindfulness plays an important role in social anxiety, and provide impetus for future research involving clinical studies of mindfulness-based interventions for social anxiety.